Nutrient content in soil and in copaiba leaves (Copaifera langsdorffii Desf.) in different phytophysionomies - Russo , Graziela Aparecida (2022)
Copaiba (Copaifera langsdorffii Desf.) has suffered from continuous extractivism due to its medicinal properties, deforestation and urban expansion, despite having important medicinal and economic characteristics, this species lacks basic information, such as its adaptation to different types of soil. The objective of this study was to evaluate the nutrient content in soil and leaves of copaiba in different phytophysiognomies (Cerradão and Semideciduous Seasonal Forest (FES)). Plant tissue and soil samples were collected in the Cerradão and FES areas for analysis. The values ​​of plant tissue nutrients were relatively similar, however, Nitrogen, Potassium, Copper and Boron were higher in FES, while in Cerradão, Calcium and Manganese was higher. The analyzes of both soils showed that they can be considered with good initial fertility due to the obtained values ​​ (V%: 50 for FES and 52 for Cerradão) in addition to show a low percentage of clay. It is expected that these data will contribute to the understanding of the plasticity that the species has under different ecological conditions.